2013
DOI: 10.2478/s11535-013-0171-8
|View full text |Cite
|
Sign up to set email alerts
|

The composition and antibacterial activity of essential oils in three Ocimum species growing in Romania

Abstract: In this study the glandular hair morphology, chemical composition and antimicrobial activity of the essential oils from three Ocimum species have been investigated (Ocimum basilicum L. var. Genovese, O. gratissimum and O. tenuiflorum). The indumentum shows little variation among the investigated species with both glandular and non-glandular hairs presents. Glandular hairs on the three species are peltate and capitate (with various cell numbers in the stalk and gland). The samples of essential oils obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 37 publications
(47 reference statements)
3
34
2
1
Order By: Relevance
“…On the other hand, Kpoviessi et al, 31 found that p-cymene was predominant in O. gratissimum, followed by thymol and γ-terpinene. The investigated chemotype differs from those reported previously, which were the eugenol type 12,27,34 , linalool type 39 , methyl cinnamate type 40 and ethyl cinnamate type 41 . Variations of the percentages of chemical constituents were observed according to daytime of collection, including major constituent as thymol (28.3-37.7 %), γ-terpinene (12.5-19.3 %) and p-cymene (12.1-18 %).…”
Section: Results and Discussion Ield And Chemical Composition Of Essecontrasting
confidence: 85%
See 1 more Smart Citation
“…On the other hand, Kpoviessi et al, 31 found that p-cymene was predominant in O. gratissimum, followed by thymol and γ-terpinene. The investigated chemotype differs from those reported previously, which were the eugenol type 12,27,34 , linalool type 39 , methyl cinnamate type 40 and ethyl cinnamate type 41 . Variations of the percentages of chemical constituents were observed according to daytime of collection, including major constituent as thymol (28.3-37.7 %), γ-terpinene (12.5-19.3 %) and p-cymene (12.1-18 %).…”
Section: Results and Discussion Ield And Chemical Composition Of Essecontrasting
confidence: 85%
“…This could be related to lower thymol content (28.3 %). The activity of O. gratissimum oil against some bacteria and fungi were also reported in previous works 11,31,39,46 . Among previously published studies, the antibacterial activity of thymol-containing oil of O. gratissimum was only reported in the work of Ngassoum and co-authors 37 against some Gramnegative and Gram-positive bacteria other than L. monocytogenes and S. Typhimurium.…”
Section: Antibacterial Activity Of Essential Oilssupporting
confidence: 81%
“…The major chemical compounds found in their study were thymol (26%), followed by g-terpinene (20%) and p-cymene (17.6%). Stefan et al (2013) analyzed the chemical composition of EO from three plants of the Ocimum genus cultivated in Romania. Linalool was also the major compound found in the EO of O. gratissimum.…”
Section: Characteristics Of Growth Field and Clove Basil Essential Oilmentioning
confidence: 99%
“…Diverse pharmacological activities, viz., anthelmintic [5], antiinflammatory, analgesic [6], immunostimulatory [7], cardiovascular [8], antimutagenic [9], antimalarial [10], antidiarrheal [11,12], antidiabetic [13], an-tioxidant [14,15], cytotoxic [16], and antimicrobial [15,[17][18][19], have been reported from the extract and essential oil of O. gratissimum. The major compound of the essential oil of O. gratissimum from different regions [15,[19][20][21][22][23][24][25][26][27][28][29][30][31] is represented in Table I. The aim of the present study was to analyze the constituents of essential oil of O. gratissimum growing in a desolate area of South India.…”
Section: Introductionmentioning
confidence: 99%